Analysis of the barriers within and outside the organization of public-private partnership in Iran - Vali Rahmani; Hamid Reza Abbasian (مهندسی و مدیریت ساخت, 2018)
Infrastructure development plays an important role in advancing the economic and social goals of societies. Developed countries have built up their infrastructure and provided plenty of resources to carry out new projects and maintain the old projects. In contrast, developing countries need to develop their own infrastructure. According to Asian Development Bank estimates, in the next decade, Asian countries will need funding to develop infrastructure of over $ 1 trillion. Obviously, governments face serious constraints on financing major projects. For this reason, the public sector tries to compensate for some of these shortcomings by employing and activating the private sector in infrastructure projects. However, there are some barriers that have slowed down the process of assigning projects, the main purpose of which is to investigate such barriers. The present study is a type of developmental-applied study. For reach method have been used the quantitative research method (factor analysis and Mann-Whitney test) have been used. The sources of documentary and library information collection and field surveys. The results show that there are eight factors of financial support and facilities, knowledge and attitudes of the parties, public sector employer, contradictory policies and instructions, financial-economic fluctuations, regulatory processes, project management, and the factors that the government has by eliminating the problems Each sector can support the private sector participation in the process of implementing civil projects in the country.